Pelatihan Regulasi Emosi Untuk Menurunkan Perilaku Marah Pada Pasien Penderita Hipertensi - Pujiyatmi, Taufik Kasturi, S.Psi., M.Si., Ph.D (2016)
All people of all cultures have angry behavior. Excessive anger can aggravate health and more risk of suffering from hypertension and can lead to rupture of blood vessels to sudden death. Despite the angry behavior is not always good and tend to harm to oneself and others, but the angry behavior if managed well and be understood can bring a positive value, one way is to emotion regulation. The purpose of this study to determine the influence of emotion regulation training to the decline of angry behavior in patients with hypertension. This study used an experimental method with tri solomon design. The subjects were patients with hypertension in the target group Griya Sehat "Ulima Medika" which amounted to 120 people. The results of this study in the experimental group and the control group 2 had a lower angry behavior compared to the control group 1. In view of the kind of age no distinction between adult angry behavior early, middle and late adulthood. Early adulthood have a higher than angry behavior and late middle age. Judging from the male sex had angry behavior higher than women. Keywords: Behavioral anger, emotion regulation training and hypertension